Recent investigations on dynamic problems for an elastic body with initial (residual) stresses (review) - Akbarov, S. D. (SPRINGER, 2007)
Recent investigations of dynamic problems for bodies with initial stresses are reviewed. These are investigations carried out over the last six years using the piecewise-homogeneous body model and the three-dimensional linearized theory of elastic waves in initially stressed bodies. Emphasis is on the investigations performed by the author and his students. The research studies on the wave propagation and dynamic time-harmonic stress-state problems are reviewed separately. The areas for further investigations are pointed out.
Keywords: composite; initial stress; residual stress; wave dispersion; layered material; fibrous material; time-harmonic stress field; Lamb's problem; WAVE-PROPAGATION; HALF-SPACE; LAMBS PROBLEM; FIELD; ELEMENT; LAYER; SLAB; STABILITY; CONSTANTS; VIBRATION; Mechanics